Decision Determinants of Tourist’s Intention to Revisit a Coastal Tourism Object by Using ROS Model: A Case of Kelapa Dua Islands Jakarta - Hendratono, Tonny; Supina, Supina (E-Journal of Tourism; Volume 4 Number 2 (September 2017)DO - 10.24922/eot.v4i2.36396, 2017)
This study examines factors in decision making of tourist to revisit Kelapa Dua Island, Thousand Islands, DKI Jakarta, Indonesia. The objectives of this study were: (1) To know the socio-demographic characteristics of the visitors in order to understand the relationship on their decision making to revisit the island, (2) To know the preferred activity preference attributes of the visitors in order to understand the relationship on their decision making to revisit the island, (3) To know the specific role of beach settings / attributes in the visitors’ view in order to understand the relationship on their decision making to revisit the island, and (4) To define the expected desired experiences of the visitors in order to understand the relationship on their decision making to revisit the island. The data collection used was primary data, taken by spreading questionnaire to 100 visitors on the exit gate of Kelapa Dua Island, DKI Jakarta, Indonesia. An accidental sampling was used to select the respondent surveyed for this study.  Sampling will be rotated on different days of the week and between morning, afternoon, and evening in attempts to acquire a more accurate and representative population.